Природа i кiнетика нестацiонарного поглинання свiтла плiвками фталоцiанiну свинцю (PbPc) і хлоралюмiнiйхлорфталоцiанiну (ClAlClPc), індукованого фемтосекундними лазерними iмпульсами - Gorishnyi, M. P. (Publishing house "Academperiodika", 2018)
Spectra of non-stationary light absorption ΔD induced by femtosecond laser pulses in lead phthalocyanine (PbPc) and chloro-aluminum-chloro-phthalocyanine (ClAlClPc) films have been studied. The 210-nm PbPc and 270-nm ClAlClPc films were thermally evaporated in a 6.5-mPa vacuum onto quartz substrates. “Hot” absorption bands induced by electron transitions from non-zero vibronic bands of state S1 into the zero vibronic band of state Sm were registered in the spectral interval of 2.04–2.37 eV. The dependences of the normalized kinetics ΔDn(t) were non-exponential for both films. The experimental curves ΔDn(t) for PbPc and ClAlClPc films are approximated by sums of two and three, respectively, exponents with different relaxation times.